Advances in the Physics of Stars - in Memory of Prof. Yuri N. Gnedin - Ikhsanov, Nazar R.; Klimchitskaya, Galina L.; Mostepanenko, Vladimir M. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint, which was edited by Prof. Dr. Nazar R. Ikhsanov, Prof. Dr. Galina L. Klimchitskaya, and Prof. Dr. Vladimir M. Mostepanenko, contains research and review articles published in a Special Issue of the journal Universe in memory of outstanding astrophysicist Prof. Dr. Yuri N. Gnedin, who organized and led the Department of Astrophysics at the famous Pulkovo Observatory of the Russian Academy of Sciences for several decades. In these articles, the reader will find new and intriguing ideas in several topical problems of astrophysics as well as comprehensive and readily accessible sketches of a few recently performed investigations.